Título Padrão - Kere, Cheik Daniel (Revista de Ciências Sociais, 2019)
Can we understand the fundamental dynamics of political change in some States on the African continent? Similar attempts exist and I have tried to understand them. By focusing on macro-social data, particularly young people - taken from a demographic perspective - I have tried to present its impact on the political field in West African French-speaking States. The demographic weight of young people, combined with some major factors, influences the political field of these States. The result is a reconfiguration of the strategy sets, but also the emergence of a gelatinous form of relatively autonomous political space. This space oscillates between autonomy and fusion with the classical political space.